Residential childcare: A new educational perspective - Paola Bastianoni (Pensa MultiMedia, 2022)
In this article we discuss the possibility to consider residential childcare context - just like other families characterized by the absence of biological generativity - as a family group, an educating family, when meaningful caregivers in a professional context guarantee parental functions to those children and adolescents who cannot have the opportunity to stay in their family of origin because of situations of deprivation, neglect or abuse. To define "residential childcare" as a "family" implies the assumption of an interpretative perspective whereby we consider all the family pluralities existing today, structured by the discontinuity between generativity, parenthood, conjugality and other variables, whose interconnection deconstructs the traditional idea of "natural" family (Fruggeri, 2007). In the light of these reflections, we can appreciate the complexity of the challenges which residential childcare is called upon to deal with, by configuring itself as one of the possible types of family.